If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 13 = 4x + 7 Reorder the terms: 13 + 7x = 4x + 7 Reorder the terms: 13 + 7x = 7 + 4x Solving 13 + 7x = 7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 13 + 7x + -4x = 7 + 4x + -4x Combine like terms: 7x + -4x = 3x 13 + 3x = 7 + 4x + -4x Combine like terms: 4x + -4x = 0 13 + 3x = 7 + 0 13 + 3x = 7 Add '-13' to each side of the equation. 13 + -13 + 3x = 7 + -13 Combine like terms: 13 + -13 = 0 0 + 3x = 7 + -13 3x = 7 + -13 Combine like terms: 7 + -13 = -6 3x = -6 Divide each side by '3'. x = -2 Simplifying x = -2
| x+5=-4x+15 | | 2(10+t)=42 | | 12x-5=5x-47 | | 10x-11=3x+17 | | 2.5x=112 | | 9x+19=4x-1 | | 2x-8=-5x-50 | | 1+10f=7f+8 | | 8.28-r=54 | | -3x+1+3(x-4)=-2(1-x)-5 | | -6-2m=20 | | 2m+7+m=6+3m+11 | | 2x^2-9x+32=0 | | 3(x+5)=2x-6 | | 3(x+15)=2x-6 | | 7y-x=28 | | logy=-3.5 | | -2.4=7+c | | 5m-9=21 | | 18-a=27 | | 3m-2=6m-4 | | x+y=91 | | -5m+15=4(8-m) | | 5*x+3*y=10 | | (4x+2y)=324 | | 91-y=81-0.5y | | 5b^3*3b^5= | | 4(2m-5)=3(2m+8) | | 4x+2y=324 | | 1x+1y=91 | | x(2x+11)=12 | | (X+2)(x-2)=5(x+4) |